The Effect of Profitability on Firm Value with Intellectual Capital as an Intervening Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange - Elly Lestari; Moeljadi Moeljadi; Sumiati Sumiati; Djumahir Djumahir (AIBPM Publisher, 2022)
The “objective of this study is to investigate the effect of profitability on firm value with intellectual capital as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange. The population are manufacturing companies that have published Corporate Governance Reports until 2018. However, some companies do not publish regularly during the observation period from 2012 to 2018. This study uses population requirements, companies do not issue Corporate Governance Reports for a maximum of 1 year. In order to obtain a population of 14 companies, all of which were used as research samples (saturated samples) with 98 observations. The analysis method used path analysis. The results demonstrated that profitability has a direct effect on firm value and profitability has an indirect effect on firm value. Intellectual capital acts as a mediating variable in this relationship. The increase in intellectual capital has an impact on increasing the value of the company. In addition, profitability can improve company performance and corporate image internally and externally, thereby increasing investor confidence, and companies have the opportunity to increase intellectual capital. The increase in intellectual capital has an impact on increasing the value of the” company. Keywords: Profitability, Intellectual Capital, Firm Value